PENGARUH TRANSPARANSI DAN AKUNTABILITAS PEMERINTAH DESA TERHADAP PENGELOLAAN ALOKASI DANA DESA - Ependi, Agus Sihan (COMPETITIVE, 2023)
This study aims to: (1) Find out how much transparency has an effect on the allocation of village funds. (2) Knowing how much influence accountability has on the allocation of village funds. (3) Knowing how much influence transparency and accountability have on the allocation of village funds. The object of this research is 10 villages located in Jampang Kulon sub-district. The data taken were 70 data consisting of: transparency, accountability and allocation of village funds. Data was collected by distributing questionnaires to each village via Google Froms. The data analysis tools used are validity and reliability tests, classical assumption tests and hypothesis testing. The results show that: (1) there is a significant positive effect of transparency on the allocation of village funds with a t-count value of 2.695 which is greater than t-table 1.994 with a significance value of 0.009; (2) there is a positive and significant effect of accountability on the allocation of village funds with a t-count value of 3.912 which is greater than the t-table value of 1.994 with a significance value of .000; (3) There is a significant positive effect between transparency and accountability on the allocation of village funds with a calculated F value of 16.360, which is greater than the F table value of 3.15 with a significant value of .000.